AVALIAÇÃO NUMÉRICA DE FATORES DE INTENSIDADE DE TENSÃO EM PROBLEMAS DE UMA TRINCAS - Silva, Welington Vital da; Gomes, Gilberto; Delgado Neto, Alvaro Martins; Ferraz de Paiva, Guilherme Oliveira (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The Fracture Mechanics has become an important analytical tool in the design and subsequent operation in structures that may develop cracks during their service life. In this regard, and based on the principle of linear elastic fracture mechanics (LEFM) and the knowledge of their stress intensity factors (FITs), this paper proposes numerically evaluate these factors from the use of two analysis programs: the well-established ABAQUS CAE package for analysis with finite element method (FEA) and an academic program called emCracker2D still under testing, using a formulation based on the dual boundary element method (DBEM) and the J-integral technique for calculating the FITs. The latter is based on object-oriented programming and written in C++ language, having an interface with MATLAB for treatment of modeling, meshing and viewing results. This work is limited to the application and use of BemCracker2D program to obtain the stress factors as proposed, and will not be addressed computational aspects related to DBEM formulation or about the program. Examples of open literature for multiple cracks models are presented, aiming to certify the efficiency and accuracy of the DBEM front of the FEM in this type of problem.